Sedimentary rhythm of Mn-carbonate laminae induced by East Asian summer monsoon variability and human activity in Lake Ohnuma, southwest Hokkaido, northern Japan. (15th November 2020) - Katsuta, Nagayoshi; Naito, Sayuri; Ikeda, Hisashi; Tanaka, Kuniaki; Murakami, Takuma; Ochiai, Shinya; Miyata, Yoshiki; Shimizu, Mayuko; Hayano, Asuka; Fukui, Konami; Hasegawa, Hitoshi; Nagao, Seiya; et al.
Abstract: Past and ongoing precipitations of Mn-carbonate (rhodochrosite) have occurred in the freshwater Lake Ohnuma, which is situated about 8 km south of the Hokkaido-Komagatake volcano, southwest Hokkaido (northern Japan). Lake sediments from a surface and a longer ∼4 m core contain the sedimentary rhythms of rhodochrosite laminae and volcanic deposits which were identified by nondestructive micro-XRF fluorescence analyses. The three tephra ash layers from the Hokkaido-Komagatake volcano, characterized by peaks of Al, Si, K, Ca, and Ti, correspond to regionally recognized tephras (1640, 1929 and 1996 CE) based on ashfall isopachs and 137 Cs, 210 Pb and 14 C ages determined from the two cores. The sedimentation rate showed a drastic change around 1929 CE; ∼0.3 cm/yr for 1640–1929 CE and ∼2.7 cm/yr for 1929–2012 CE. The Mn content record of Lake Ohnuma sediments, composed of rhodochrosite laminae, showed a periodic variation with a decadal–centennial scale over the interval 1640–2012 CE. Sediment petrography and hydrochemical measurements suggest that the metastable phase of rhodochrosite was deposited during summer after being precipitated, followed by the crystal growth of rhodochrosite within the anoxic sediments. On the basis of these results, high Mn content is interpreted as an indicator of strengthened summer stratification associated with reduced rainfall runoff. The Ti/Si ratios are representative of the relative abundance of detrital inputs from the watershed. The combined signals of elevated Mn content and Ti/Si ratio for 1935–2012 CE indicate eutrophication and hypoxia in the lake and enhanced land erosion in the watershed, associated with the post-1970s intensive land use such as livestock farming. For 1640–1935 CE, the Lake Ohnuma record shows an antiphase relationship between the Mn content and Ti/Si ratio, which implies that the detrital inputs reflected the strength of the East Asian summer monsoon (EASM), and the reduced rainfall runoff resulted in weaker mixing, followed by depleted O2 in the water column. The antiphase variation in Mn content and Ti/Si ratio suggest weak EASM during the Little Ice Age (∼1850 CE), followed by strong EASM between 1860 and 1929 CE. Highlights: Lake Ohnuma sediments contain Ko-d (1640 CE), Ko-a (1929 CE), and 1996 CE tephra deposits. These deposits originated from the Hokkaido-Komagatake volcano. Sediments recorded EASM over 1640–1935 CE, then anthropogenic signals over 1935–2012 CE. Rhodochrosite is precipitated in hypoxic hypolimnion during summer stratification. Rhodochrosite laminae formation coincides with weaker EASM precipitation phases.